2018
DOI: 10.5812/ijpbs.9975
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Depression in Pregnant Iranian Women: A Systematic Review and Meta-Analysis

Abstract: Context: Depression is a common problem during pregnancy. Depression has several adverse effects on the mother and infant. Evidence Acquisition: The present study was conducted to investigate the prevalence of depression in pregnant women in Iran. Methods: This study was performed based on the Preferred Reporting Items for systematic reviews and meta-analyses (PRISMA) guidelines. We searched the literature in the national and international databases, including Magiran, Iranmedex, SID, Medlib, IranDoc, Scopus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 23 publications
3
21
0
1
Order By: Relevance
“…Observed differences are due to different sampling. In addition, differences in measured parameters in different populations can be the reasons of heterogeneity in this study (45)(46)(47).…”
Section: Discussionmentioning
confidence: 96%
“…Observed differences are due to different sampling. In addition, differences in measured parameters in different populations can be the reasons of heterogeneity in this study (45)(46)(47).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the findings of our study may not be generalizable to the other regions and the whole population of Tehran.Our finding of an 8.8% C. trachomatis infection rate in the present study is consistent with results from studies conducted within the past two decades across Iran. In a meta-analysis on reports of C. trachomatis infection rate among pregnant Iranian women, the overall prevalence of C. trachomatis infection has been reported to be 8.74% (95%CI: 5.40 -13.84) (16). However, the prevalence estimate of C. trachomatis infection that we report in this study is moderate in comparison to those reported previously in this region (2.2% and 3.3% by Khezerdoust et al,11.1% by Rashidi et al, and 11.2% by Chamani et al) (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies carried out in Iran, some risk factors were recognized for HBV and HCV infection such as the history of imprisonment, unemployment, low educational level, injection of drug use, and unprotected sex (19)(20)(21). In a review of another study that evaluated the risk factors for HBV infection among pregnant women, illiteracy, occupation, abortion, history of blood transfusion, and addiction of spouse were known as significant risk factors (22). In another study conducted in general population of BIrjand, the prevalence of anti-HBc seropositivity was significantly higher in subjects with a lower level of education, intravenous (IV) drug users, older subjects, subjects with piercings, and those with a history of familial HBV or HCV infection.…”
Section: Discussionmentioning
confidence: 99%